Effects of cold treatments on fitness and mode of reproduction in the diploid and polyploid alpine plant Ranunculus kuepferi (Ranunculaceae) - Klatt, Simone (Ann Bot, 2018)
BACKGROUND AND AIMS: Alpine plants grow in harsh environments and are thought to face occasional frost during the sensitive reproductive phase. Apomixis (asexual reproduction via seed) can be advantageous when sexual reproduction is disturbed by cold stress. Apomictic polyploids tend to grow in colder climates than their sexual diploid relatives. Whether cold temperatures actually induce apomixis was unknown to date. METHODS: We tested experimentally in climate cabinets for effects of low temperatures and repeated frost on phenology, fitness and mode of reproduction in diploid and tetraploid cytotypes of the alpine species Ranunculus kuepferi. The reproduction mode was determined via flow cytometric seed screening (FCSS). KEY RESULTS: Diploids produced the first flowers earlier than the tetraploids in all treatments. Cold treatments significantly reduced the fitness of both cytotypes regarding seed set, and increased the frequency of apomictic seed formation in diploids, but not in tetraploids. Over consecutive years, the degree of facultative apomixis showed individual phenotypic plasticity. CONCLUSIONS: Cold stress is correlated to expression of apomixis in warm-adapted, diploid R. kuepferi, while temperature-tolerant tetraploids just maintain facultative apomixis as a possible adaptation to colder climates. However, expression of apomixis may not depend on polyploidy, but rather on failure of the sexual pathway.